2022
DOI: 10.1186/s12964-022-00898-0
|View full text |Cite
|
Sign up to set email alerts
|

NEK2 promotes the migration and proliferation of ESCC via stabilization of YAP1 by phosphorylation at Thr-143

Abstract: Background Esophageal Squamous Cell Carcinoma (ESCC) was characterized as a regional-prevalent and aggressive tumor with high morbidity and mortality. NIMA-related kinase 2 (NEK2) is an interesting oncogene, the alteration of which leads to patients-beneficial outcomes. We aimed to explore the role of NEK2 in ESCC and excavate its mechanism. Methods RNA-seq data were downloaded from TCGA and GEO and analyzed by R software. The protein levels were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…NEK2 overexpression has been found in various human malignancies [73][74][75][76][77][78][79][80], including gastrointestinal tumors [81,82]. Aberrant NEK2 expression in cancers has been associated with tumor cell proliferation [83], migration [82], invasion [74,77], drug/radio resistance [84,85], immune response [80,86], and poor prognosis [26,75]. In our bioinformatics analyses, NEK2 is the most frequently upregulated NEK member in EAC (significantly detected in seven of the eight databases).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…NEK2 overexpression has been found in various human malignancies [73][74][75][76][77][78][79][80], including gastrointestinal tumors [81,82]. Aberrant NEK2 expression in cancers has been associated with tumor cell proliferation [83], migration [82], invasion [74,77], drug/radio resistance [84,85], immune response [80,86], and poor prognosis [26,75]. In our bioinformatics analyses, NEK2 is the most frequently upregulated NEK member in EAC (significantly detected in seven of the eight databases).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, NEK2 may also play a role in microtubule stabilization [70], B cell development and immunological response [71], and splicing [72]. NEK2 overexpression has been found in various human malignancies [73][74][75][76][77][78][79][80], including gastrointestinal tumors [81,82]. Aberrant NEK2 expression in cancers has been associated with tumor cell proliferation [83], migration [82], invasion [74,77], drug/radio resistance [84,85], immune response [80,86], and poor prognosis [26,75].…”
Section: Discussionmentioning
confidence: 99%
“…The NIMA-related kinase (NEK) 2, a serine/threonine kinase belonging to the NEK family, exhibits specific localization at the centrosome. It is widely acknowledged as a multifunctional protein involved in regulating various aspects of the cell cycle [6][7][8][9][10]. NEK2 as multiple research studies have consistently observed its increased expression in different types of cancers and its correlation with poor overall survival results [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The NIMA-related kinase (NEK) 2, a serine/threonine kinase belonging to the NEK family, exhibits specific localization at the centrosome [6]. NEK2 is widely acknowledged as a versatile protein involved in the regulation of various aspects of cell cycle, including replication and segregation of centrosomes, stabilization of microtubules, attachment of kinetochores, and activation of the spindle assembly checkpoint [7][8][9][10]. In the realm of scientific academia, there has been considerable focus on the significant involvement of NEK2 in the development of tumors in recent years.…”
mentioning
confidence: 99%
“…2021) Never in mitosis-related kinase 2 (NEK2) is a serine/threonine kinase that facilitates the division of centrosomes and guarantees the accurate segregation of chromosomes in the G2/M phase of the cell cycle(Xia et al 2015). The prognostic signi cance of increased NEK2 expression and its role in ESCC in proliferation, migration, and EMT was demonstrated in a study by Su W et al They concluded that NEK2 interacts with YAP1 and phosphorylates it at Thr-143, thereby attenuating its ubiquitylation in vitro and promoting its stability, thereby mediating the progression of ESCC(Su et al 2022). Previous studies have indicated that NEK2 inhibitors e ciently inhibit cancer cell proliferation by causing arrest of the cellular cycle and apoptotic cell death, and markedly inhibition of tumor growth in-vivo(Xi et al 2017;Fang et al 2016).…”
mentioning
confidence: 99%